Brand experiential marketing influencing values of boutique hotels - WIANGKHAM, TIPKANOK; Kerdsiri Charoenwisan, Kerdsiri (Journal of Rattana Bundit University, 2022)
The hotel sector has been growing recently and is a significant component of Thailand's tourism industry. However, times have changed. Hotel executives must learn and drive their businesses to keep up with technology, focusing on using artificial intelligence technology to create personalized experiences, deliver exceptional service beyond expectations, understand the needs of tourists, and constantly adapt to changes. Boutique hotels are small accommodations that are one-of-a-kind in terms of design, location, and service, and they cater to customers with special needs for a specific product or service. This research investigated the concepts of experiential marketing, brand experience, experiential online marketing, and brand loyalty. Experiential marketing in the boutique hotel industry focuses on using online social media to communicate with customers from the advertising process with various marketing strategies until the customer decides to acquire the service. At the same time, customers share their stories and positive service experiences with others through social media. This creates an endless cycle of service and boosts the bottom line of boutique hotels. The boutique hotel experiential marketing is a combination of the advantages of the online world and the strengths of the offline world, which helps to enhance the offline business even more.